The Art Metropole : The Top 100. - Bronson, AA; Gale, Peggy; Scott, Kitty; Shaughnessy, Jonathan (Ottawa : National Gallery of Canada Ottawa, 2006)
Abramovic, Marina ; Anderson, Laurie ; Antin, Eleanor ; Art & Language ; Askevold, David ; Baldessari, John ; Barry, Robert ; Baxter, Iain ; Beuys, Joseph ; Birnbaum, Dara ; Bloom, Barbara ; Boetti, Alighiero ; Boltanski, Christian ; Brecht, George ; Broodthaers, Marcel ; Burden, Chris ; Buren, Daniel ; Byars, James Lee ; Cage, John ; Calle, Sophie ; Campbell, Colin ; Chitty, Elisabeth ; Clark, Larry ; Craig, Kate ; Curnoe, Greg ; Darboven, Hanne ; Dibbets, Jan ; Duchamp, Marcel ; Falardeau, Pierre ; Feldmann, Hans-Peter ; Fritsch, Katharina ; Fulton, Hamish ; General Idea ; Gilbert & George ; Gober, Robert ; Goldstein, Jack ; Gonzalez-Torres, Felix ; Graham, Dan ; Graham, Rodney ; Guerrilla Girls ; Harding, Noel ; Holzer, Jenny ; Hsieh, Tehching ; Johnson, Ray ; Kaprow, Allan ; Kennedy, Garry Neill ; Kippenberger, Martin ; Klein, Yves ; Knoebel, Imi ; Knowles, Alison ; Kosuth, Joseph ; Kruger, Barbara ; Levine, Les ; Levine, Sherrie ; LeWitt, Sol ; Lexier, Micah ; Lum, Ken ; Maciunas, George ; Marclay, Christian ; Martin, Agnes ; Matta-Clark, Gordon ; Morris, Michael ; Morris, Robert ; Murray, Ian ; N.E. Thing Co. ; Nannucci, Maurizio ; Nauman, Bruce ; Nihilist Spasm Band ; Nitsch, Hermann ; Oldenburg, Claes ; Ono, Yoko ; Opalka, Roman ; Oppenheim, Dennis ; Oppenheim, Meret ; Piper, Adrian ; Poulin, Julien ; Rauschenberg, Robert ; Richter, Gerhard ; Rosler, Martha ; Ruscha, Edward ; Sherman, Tom ; Singleton, Becky ; Situationistische Internationale ; Smithson, Robert ; Snow, Michael ; Spoerri, Daniel ; Steele, Lisa ; Sterbak, Jana ; Sullivan, Derek ; Trasov, Vincent ; Trockel, Rosemarie ; Wall, Jeff ; Warhol, Andy ; Weiner, Lawrence ; Wieland, Joyce ; Wool, Christopher ; Young, La Monte
Engels
Exhibition. Art Metropole : The Top 100. National Gallery of Canada Ottawa, 01.12.2006 - 25.02.2007.
boek
Keywords: General Idea